Analysis of emotional fluctuations in infertile women during ART treatment: the impact of ovarian hyperstimulation - Xinyu Zhou; Sen Liang; Dongmei Ji; Chunmei Liang; Yunxia Cao (Journal of Psychosomatic Obstetrics and Gynecology)
Background Infertility affects many reproductive-aged couples, with assisted reproductive technology (ART) offering hope but also significant emotional stress due to invasive procedures, hormonal fluctuations, uncertainty, and financial and emotional burden of repeated cycles. Ovarian hyperstimulation syndrome (OHSS), a common ART complication, may further aggravate psychological distress, yet its mental health impact remains understudied.Methods This longitudinal study included 1,429 women undergoing their first ART cycle at a reproductive center in China. Psychological assessments were conducted at four critical time points: before ART, post-surgery (early pregnancy), mid-pregnancy and late pregnancy. Validated scales (SAS, CES-D, CPSS, PSQI) measured anxiety, depression, stress, and sleep quality. OHSS was diagnosed per clinical guidelines. Generalized estimating equations (GEEs) assessed changes over time and the moderating effects of OHSS, adjusting for age, education level and income.Results OHSS occurred in 9.2% of participants, who tended to be younger and have higher socioeconomic status. Anxiety peaked after surgery and remained elevated; stress declined steadily; sleep quality improved; depression rebounded slightly in late pregnancy. OHSS significantly intensified anxiety and stress but had no clear impact on depression or sleep.Conclusions Emotional responses during ART are dynamic. OHSS amplifies anxiety and stress, warranting integrated psychological support within ART programs, particularly for OHSS-affected women.